Uji air perasan jeruk kesturi (Citrus microcarpa Bunge.) terhadap perubahan warna resin komposit yang direndam dalam larutan kopi (e-GiGi, 2017)
Abstract: Color change or discoloration of the tooth surface is an aesthetic problem that is often complained because it reduces one’s confidence in terms of appearance. This problem can also occur on the surface of restorative materials inter alia composite resin. Composite resin is a tooth-colored restorative material that most people favor due to its aesthetic value. This discoloration can occur due to excessive intake of colored beverages like coffee. The treatment used for discoloration is bleaching, but these treatments have side effects. Calamondin (Citrus microcarpa Bunge.) can be an alternative bleaching agent because it contatins citric acid. This study was aimed to determine whether calamondin juice could affect the color change of composite resin soaked in coffee solution. This was a pre-experimental study with a one shot case study design. Samples were 10 composite resins with a diameter of 5 mm and 2 mm thick soaked in coffee solution for 7 days to obtain discoloration and then samples were soaked in calamondin juice for 5 days to whiten the samples. The discoloration was measured by using the CIEL*a*b* method at 60 minutes and 5 days after soaking in calamondin juice. The Friedman test showed significant changes (p